Comparative analysis of Ukraine’s and Poland revenues of local budgets formation under conditions of decentralization (Economics and region, 2024)
Ukraine’s European integration processes began to be actively implemented after its independence and require significant changes in national policy. Reforms are being implemented in most spheres of the country’s activity, so after the signing of the Association Agreement with the EU in 2015, 17 national reforms were introduced, one of which was the decentralization reform, which caused changes in the administrative and territorial structure of Ukraine. The scientific article examined the revenue part of the local budgets of Ukraine and Poland formation and conducted a comparative analysis of the main differences in the budget-forming components of these countries (the share of local budgets to the consolidated budget, the share of own funds and investment funds from the European Union, the share of tax revenues to the total revenues of the local budget). The Polish model of decentralization reform implementation was chosen as the basis for the implementation of the decentralization model in Ukraine. It was determined that the formation of local budgets in Poland has a stable character and is formed equally by the support of the central government, investments and the tax part. ncomes to local Poland budget over the past 5 years have been stable, in particular, the share of tax revenues is in the range of 31-34%, the share of investments from the EU - 4-6%, the share of own revenues - 49-51%.Local budgets of Ukraine under the conditions of decentralization are mostly formed at the expense of taxes, in particular, their specific weight is 56% on average over the last 5 years. Despite the fact that the Polish model serves as a model for the Ukrainian decentralization reform, the results of its implementation are radically different in both countries. The main factors affecting the effectiveness of this reform implementation are different initial conditions, different statuses of countries and hostilities on the territory of Ukraine. However, analyzing the financial indicators of Ukraine, it can be stated that the country has a high potential to achieve stable economic indicators in the post-war period.
Keywords: decentralization; reform; local budgets; income; local self-government bodies